Complete pathological response to neoadjuvant chemoradiotherapy is associated with improved long-term survival after surgical treatment for rectal cancer - Khajeh, Elias; Fakour, Sanam; Zeh-Ressel, Constanze; Jafari, Marzieh; Nikbakhsh, Rajan; Ramouz, Ali; Mehrabi, Arianeb; Büchler, Markus W.; Kulu, Yakup (Surgical oncology, 2025)
Background - Tumor regression after neoadjuvant chemoradiotherapy can improve the long-term outcomes of rectal cancer. However, it is unclear how the tumor regression grade (TRG) relates to long-term outcomes. We evaluated how the TRG affects overall survival in patients with rectal cancer who underwent neoadjuvant chemoradiotherapy prior to radical surgery. - Methods - All patients who underwent low anterior resection for rectal cancer after chemoradiotherapy over a 13-year period were included in this study. Perioperative and histopathological data of patients, including the TRG (categorized as no regression, minimal regression, moderate regression, near complete regression and complete regression) were evaluated. The correlation of TRG with overall survival was assessed using the log-rank test and Cox proportional hazards regression analysis. - Results - During the study period,193 patients underwent low anterior rectal resection after neoadjuvant chemoradiotherapy. The 90-day mortality rate was 1.5 % and the median follow up was 69.5 months. The 5-year and 10-year overall survival rates were 85.0 % and 69.8 %, respectively. Patients with complete regression had a significantly higher 10-year overall survival rate than other patients (87.3 % vs. 66.5 %, p = 0.031). Multivariate analysis revealed that older age (hazard ratio [HR] = 2.4,95 % confidence interval [95 % CI] = 1.3-4.6, p = 0.007) and complete pathological response (HR = 0.23, 95 % CI = 0.06-0.96, p = 0.044) were independent predictors of overall survival. - Conclusion - Complete pathological response after neoadjuvant therapy for rectal cancer improves overall survival after surgery. Further studies are needed to determine the factors that predict complete TRG to identify patients who would benefit most from neoadjuvant chemoradiotherapy.